(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article deals with the process of formation of new dynastic myth and my-thology of Queen Elizabeth I’s dynastic reign. The author notes that the reason of the success of Elizabeth’s reign was due to the existence of well thought out court policy of conveying an image of the queen in a non-negative light. It is shown that in the process of forming new courtly habits, important roles were played by Tudor "propaganda", especially with literary and historical portraiture. The author concludes that due to the spread of certain ideas and views, the image of the Queen was presented to the public as the "perfect" Keeper of England and the "ideal" royal virtues.